Proteomics on brefeldin A-treated Arabidopsis roots reveals profilin 2 as a new protein involved in the cross-talk between vesicular trafficking and the actin cytoskeleton - Takác, Tomás; Pechan, Tibor; Richter, Hendrik; Müller, Jens; Eck, Carola; Böhm, Nils; Obert, Bohus; Ren, Haiyun; Niehaus, Karsten; Samaj, Jozef (Journal of proteome research, 2011)
The growing importance of vesicular trafficking and cytoskeleton dynamic reorganization during plant development requires the exploitation of novel experimental approaches. Several genetic and cell biological studies have used diverse pharmaceutical drugs that inhibit vesicular trafficking and secretion to study these phenomena. Here, proteomic and cell biology approaches were applied to study effects of brefeldin A (BFA), an inhibitor of vesicle recycling and secretion, in Arabidopsis roots. The main aim of this study was to obtain an overview of proteins affected by BFA, but especially to identify new proteins involved in the vesicular trafficking and its cross-talk to the actin cytoskeleton. The results showed that BFA altered vesicular trafficking and caused the formation of BFA-compartments which was accompanied by differential expression of several proteins in root cells. Some of the BFA-up-regulated proteins belong to the class of the vesicular trafficking proteins, such as V-ATPase and reversibly glycosylated polypeptide, while others, such as profilin 2 and elongation factor 1 alpha, are rather involved in the remodeling of the actin cytoskeleton. Upregulation of profilin 2 by BFA was verified by immunoblot and live imaging at subcellular level. The latter approach also revealed that profilin 2 accumulated in BFA-compartments which was accompanied by remodeling of the actin cytoskeleton in BFA-treated root cells. Thus, profilin 2 seems to be involved in the cross-talk between vesicular trafficking and the actin cytoskeleton, in a BFA-dependent manner.
Keywords: Subcellular Fractions; Cytoskeleton; 2D gelová elektroforéza; Profilins; Arabidopsis Proteins; proteom; cytoskelet; subcelulární frakce; Proteome; Plant Proteins; Protein Transport; proteomika; signální transdukce; Signal Transduction; proteiny huseníčku; rostlinné proteiny; transport proteinů; Proteomics; Plant Roots; aktiny; Actins; Electrophoresis, Gel, Two-Dimensional; profiliny; Arabidopsis; Brefeldin A; kořeny rostlin; brefeldin A